The Princess Encyclopedia - Casey, Jo; Hester, Beth Landis; Saunders, Catherine (London DK, 2010)
Step inside the pages of this elegant encyclopedia to discover all you ever wanted to know about your favorite Disney princesses
English Stories
Keywords: English stories